Practical Training Report : The effectiveness of using database technology for student repayment loan scheme in HIED Unit, Sarawak Foundation / Mohd Hazwan Basrol - Basrol, Mohd Hazwan (Universiti Teknologi MARA, Sarawak, 2011)
Sarawak foundation is one of the government organizations that have a huge field in the administration and also in financial service in Sarawak especially in education and community service. Sarawak foundation is the organization that providing loans and subsidies to student who want to further their studies in universities and college. Furthermore, Sarawak foundation is responsible to be the organization to promote the education to people especially in rural area. The reason I choose Sarawak foundation to be my industrial training course is to learn and gain my experience in real working environment as well as Sarawak foundation can give me more information about how to deal with people, customers and so forth.